Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s41999-021-00477-5
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to optimize medication use in nursing homes: a narrative review

Abstract: Purpose Polypharmacy, medication errors and adverse drug events are frequent among nursing home residents. Errors can occur at any step of the medication use process. We aimed to review interventions aiming at optimization of any step of medication use in nursing homes. Methods We narratively reviewed quantitative as well as qualitative studies, observational and experimental studies that described interventions, their effects as well as barriers and enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 90 publications
(153 reference statements)
1
12
0
Order By: Relevance
“…and the feasibility of their large-scale implementation are not well established. 35,36 As previously reported, the pattern of individual PIM indicators differed according to the place of residence. 25,37 This difference could be related to distinct goals and organization of care between the community and NH.…”
Section: Factors Associated With Pims In Nhs and In The Communitymentioning
confidence: 63%
See 1 more Smart Citation
“…and the feasibility of their large-scale implementation are not well established. 35,36 As previously reported, the pattern of individual PIM indicators differed according to the place of residence. 25,37 This difference could be related to distinct goals and organization of care between the community and NH.…”
Section: Factors Associated With Pims In Nhs and In The Communitymentioning
confidence: 63%
“…In CDOAs, randomized controlled trials have also demonstrated that pharmacist intervention, computerized clinical decision support information, and multifaceted interventions were effective in reducing PIMs 35 . However, as ADRs are multifactorial, the direct impact of these interventions on clinical outcomes (such as hospitalization, quality of life, and ADRs) and the feasibility of their large‐scale implementation are not well established 35,36 …”
Section: Discussionmentioning
confidence: 99%
“…In the United Kingdom, the NHS Long-Term plan commits to increasing the number of pharmacists in primary ). Yet, there are suggestions that mandatory strategies may be more effective than guidance or recommendations at supporting medicine review practices (Spinewine et al, 2021). The impact of national guidance will need to be monitored to see if legislation is needed to support evidence-based guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of interventions to optimize medications in nursing homes have been identified (Spinewine et al, 2021): micro-level interventions, such as medication review or patientcentered care, and macro-level interventions, such as guidelines and legislation (defined as change in reimbursement, initiation of public reporting of antipsychotic use). Some examples of microlevel interventions are reported in five recent multicenter trials in Europe, which involved multidisciplinary interventions consisting of education of healthcare providers and medication reviews (Fog et al, 2017;Wouters et al, 2017;Cool et al, 2018;Husebø et al, 2019;Strauven et al, 2019); these interventions showed positive effects on reduction of the number of drugs by 9% and PIMs by 65%.…”
Section: Deprescribing In Nursing Homesmentioning
confidence: 99%